METHOD OF AUTOMATICALLY CONTROLLING THE DESCENT PHASE OF AN AIRCRAFT USING AIRCRAFT AVIONICS EXECUTING A DESCENT ALGORITHM - Darnell Mark Lawrence; Ali Sherif Fouad (2017)
A method of controlling the flight of an aircraft by automatically controlling the descent phase of an aircraft using a Flight Management System and Flight Guidance System (FMS & FGS) to control the air speed of the air craft and respond to an over speed condition.